Menanamkan Nilai Nasionalisme Melalui Pembelajaran Sejarah Perjuangan Bangsa pada Siswa Madrasah Ibtidaiyah: Sebuah Studi Tindakan Kelas - Misdawati, Misdawati (Yayasan Zia Salsabila, 2022)
The history of the nation's struggle plays a significant role in enhancing the civic attitudes of students in Islamic elementary schools. The central issue addressed in this study is how history education can instill nationalism values in students at the primary level and how the classroom action research (CAR) method can be applied to support this process. This study employed a qualitative approach with a classroom action research design, involving sixth-grade students at an Islamic elementary school (Madrasah Ibtidaiyah) in Kendari as research subjects. Data were collected through observation, interviews, and documentation, and were analyzed inductively by categorizing findings into relevant themes. The results indicate that a history-based learning model focused on the national struggle is effective in improving students’ understanding and nationalist attitudes. Students demonstrated increased active participation, a sense of pride in their country, and greater awareness of the importance of maintaining national unity. Consequently, history learning not only enhanced cognitive knowledge but also contributed to the development of students’ national character. This research provides meaningful implications for curriculum development and instructional practices in madrasah settings and offers recommendations for future studies.